Compromised autophagy precedes meniscus degeneration and cartilage damage in mice. Issue 11 (November 2017) - Meckes, J.K.; Caramés, B.; Olmer, M.; Kiosses, W.B.; Grogan, S.P.; Lotz, M.K.; D'Lima, D.D.
Summary: Objective: Autophagy is a cellular homeostasis mechanism that facilitates normal cell function and survival. Objectives of this study were to determine associations between autophagic responses with meniscus injury, joint aging, and osteoarthritis (OA), and to establish the temporal relationship with structural changes in menisci and cartilage. Methods: Constitutive activation of autophagy during aging was measured in GFP-LC3 transgenic reporter mice between 6 and 30 months. Meniscus injury was created by surgically destabilizing the medial meniscus (DMM) to induce posttraumatic OA in C57BL/6J mice. Levels of autophagy proteins and activation were analyzed by confocal microscopy and immunohistochemistry. Associated histopathological changes, such as cellularity, matrix staining, and structural damage, were graded in the meniscus and compared to changes in articular cartilage. Results: In C57BL/6J mice, basal autophagy was lower in the meniscus than in articular cartilage. With increasing age, expression of the autophagy proteins ATG5 and LC3 was significantly reduced by 24 months. Age-related changes included abnormal Safranin-O staining and reduced cellularity, which preceded structural damage in the meniscus and articular cartilage. In mice with DMM, autophagy was induced in the meniscus while it was suppressed in cartilage. Articular cartilage exhibited the most profound changes in autophagy and structure that preceded meniscus degeneration. Systemic administration of rapamycin to mice with DMM induced autophagy activation in cartilage and reduced degenerative changes in both meniscus and cartilage. Conclusion: Autophagy is significantly affected in the meniscus during aging and injury and precedes structural damage. Maintenance of autophagic activity appears critical for meniscus and cartilage integrity.